HIRÂBAH DAN HUBUNGANNYA DENGAN HUKUMAN TA‘ZÎR BAGI PELAKU KORUPSI DALAM HUKUM PIDANA ISLAM (Kajian Tafsir Ahkam Terhadap QS. al-Mâidah Ayat 33) - Endang Jumali (Asy-Syari'ah, 2016)
In Islamic criminal law perspective, the corruption can be categorized as criminal acts referred to hirâbah. Today the emerging discourse of the death penalty for coruptor as ever be discussed by NU and Muhammadiyah that are trying to resurrect its determination to fight corruption in Indonesia. The problem is whether it is governed by Islamic law? This needs to be answered whether there is a legal basis for corruptor that to be given such a heavy sanction the death penalty? Based on this, the author intends to explain how the meaning hirâbah in QS. al-Maidah verse 33 and its relationship with ta'zir penalties for perpetrators of corruption. The resultof this study can be concluded that corruption can be categorized as hirâbah. The most appropriate sanction needs to be be given to the hirâbah or corrupt stated in the QS. al-Maidah verse 33. The verse of hirâbah sanctions there are four kinds: a) killed; b) crucified; c) cut their hands and feet are crossed; and d) be removed to outside country. However, the classification of types of sanctions for corruption acts are committed by the offender, the scholars different views in order with degree and level.